Assessment of the Interrelations Between Health and Housing Conditions in a Hungarian Roma Settlement - Csaba Bálint (DETUROPE)
Health is our most important value and resource – its preservation and development are crucial in terms of our quality of life and work. Health status is mainly influenced by lifestyle, health consciousness and the healthcare system, the accessibility and quality of health-related services. Rich literature discusses the relationship between housing conditions and health status as well. The disadvantaged socio-economic situation causes deteriorated living environments and, hence, the decline in health. Through the case of the Hungarian village of Bag and the Roma settlement located there, I would like to highlight the connection between housing conditions and health.